Detection of Crohn's typical Anti-Yeast Glycan Antibodies by a novel Assay based on Flow Cytometry - Roth, Dominik; Lindemann, Aylin; Goesswein, S.; Neurath, Markus; Armbruster, F. P.; Leppkes, Moritz (Mycoses, 2021)
CRIS-Team WoS Importer:2021-10-08

Integrin αVβ6: Autoantigen and Driver of Epithelial Remodeling in Colon and Bile Ducts in Primary Sclerosing Cholangitis and Inflammatory Bowel Disease. - Roth, Dominik; Düll, Miriam; Horst, Ludwig J.; Lindemann, Aylin; Malzer, Xenia; Koop, Kristina; Zundler, Sebastian; Vetter, Marcel; Jefremow, André; Atreya, Raja; Geppert, Carol-Immanuel; Weidemann, Sören; et al. (Journal of Crohns & Colitis, 2025)
BACKGROUND: Recently, autoantibodies directed against the epithelial adhesion protein integrin αVβ6 have been identified that are strongly associated with ulcerative colitis (UC). We aimed to elucidate whether anti-integrin αVβ6 (anti-αVβ6) is present in primary sclerosing cholangitis (PSC), its associated inflammatory bowel disease, or other cholestatic liver diseases and their persistence after proctocolectomy. METHODS: We detected anti-αVβ6 by an enzyme-linked immunosorbent assay in sera collected at 2 German tertiary centers, including healthy controls (N = 62), UC (N = 36), Crohn's disease (CD, N = 65), PSC-inflammatory bowel diseases (IBD) (78 samples from N = 41 patients), PSC without IBD (PSC, 41 samples from N = 18 patients), primary biliary cholangitis (PBC, N = 24), autoimmune hepatitis (AIH, N = 32), secondary sclerosing cholangitis (SSC, N = 12), and metabolic dysfunction-associated steatotic liver disease (MASLD, N = 24). In addition, sera after proctocolectomy were studied (44 samples/N = 10 patients). Immunofluorescent analyses were performed in tissue samples from liver, large bile duct from surgical resections, and colon of PSC patients. RESULTS: Anti-αVβ6 occurred in 91% of UC, 17% of CD, 73% of PSC-IBD, 39% of PSC, 4% of PBC, 14% of AIH, and 0% of healthy controls, SSC, or MASLD. Integrin αVβ6 is selectively expressed in disease-associated epithelia of both bile duct and colon. Anti-αVβ6 levels correlate moderately with intestinal disease activity in PSC-IBD, but only weakly with biliary disease. CONCLUSIONS: Anti-αVβ6 frequently occurs in patients suffering from PSC, especially in PSC-IBD. Anti-αVβ6 levels positively correlate to IBD activity in PSC-IBD, but may also occur in the absence of clinically manifest IBD in PSC.
EVALuna2:578869

Neutrophils prevent rectal bleeding in ulcerative colitis by peptidyl-arginine deiminase-4-dependent immunothrombosis - Leppkes, Moritz; Lindemann, Aylin; Goesswein, Stefanie; Paulus, Susanne; Roth, Dominik; Hartung, Anne; Liebing, Eva; Zundler, Sebastian; Gonzalez-Acera, Miguel; Patankar, Jay; Mascia, Fabrizio; Scheibe, Kristina; et al. (Gut, 2021)
Objective Bleeding ulcers and erosions are hallmarks of active ulcerative colitis (UC). However, the mechanisms controlling bleeding and mucosal haemostasis remain elusive. Design We used high-resolution endoscopy and colon tissue samples of active UC (n = 36) as well as experimental models of physical and chemical mucosal damage in mice deficient for peptidyl-arginine deiminase-4 (PAD4), gnotobiotic mice and controls. We employed endoscopy, histochemistry, live-cell microscopy and flow cytometry to study eroded mucosal surfaces during mucosal haemostasis. Results Erosions and ulcerations in UC were covered by fresh blood, haematin or fibrin visible by endoscopy. Fibrin layers rather than fresh blood or haematin on erosions were inversely correlated with rectal bleeding in UC. Fibrin layers contained ample amounts of neutrophils coaggregated with neutrophil extracellular traps (NETs) with detectable activity of PAD. Transcriptome analyses showed significantly elevated PAD4 expression in active UC. In experimentally inflicted wounds, we found that neutrophils underwent NET formation in a PAD4-dependent manner hours after formation of primary blood clots, and remodelled clots to immunothrombi containing citrullinated histones, even in the absence of microbiota. PAD4-deficient mice experienced an exacerbated course of dextrane sodium sulfate-induced colitis with markedly increased rectal bleeding (96 % vs 10 %) as compared with controls. PAD4-deficient mice failed to remodel blood clots on mucosal wounds eliciting impaired healing. Thus, NET-associated immunothrombi are protective in acute colitis, while insufficient immunothrombosis is associated with rectal bleeding. Conclusion Our findings uncover that neutrophils induce secondary immunothrombosis by PAD4-dependent mechanisms. Insufficient immunothrombosis may favour rectal bleeding in UC.
CRIS-Team WoS Importer:2021-12-17

Neutrophils prevent rectal bleeding in Ulcerative Colitis by peptidyl-arginine deiminase-4-dependent immunothrombosis - Leppkes, Moritz; Lindemann, Aylin; Goesswein, S.; Paulus, S.; Roth, Dominik; Hartung, A.; Liebing, Eva; Zundler, Sebastian; Gonzalez Acera, Miguel; Patankar, Jay; Mascia, Fabrizio; Scheibe, Kristina; et al. (JOURNAL OF CROHNS & COLITIS, 2022)
CRIS-Team WoS Importer:2022-05-13

Protective effect of the novel calcineurin inhibitor voclosporin in experimental colitis - Lindemann, Aylin; Roth, Dominik; Koop, Kristina; Neufert, Clemens; Zundler, Sebastian; Atreya, Raja; Neurath, Markus; Leppkes, Moritz (Frontiers in Medicine, 2023)
Background and aims: Acute severe steroid-refractory ulcerative colitis remains a medically challenging condition with frequent need of surgery. It can be treated with the calcineurin inhibitor cyclosporine A with the need for therapeutic drug monitoring and significant toxicity. Recently, a novel calcineurin inhibitor, voclosporin, has been approved for the treatment of lupus nephritis with no need for therapeutic drug monitoring and an improved long-term safety profile. However, the therapeutic effect of voclosporin in acute severe steroid-refractory ulcerative colitis is still uncertain. We aimed to assess the therapeutic potential of voclosporin to ameliorate inflammation in an experimental model of colitis. Methods: We used the dextran sodium sulfate-induced model of colitis in C57BL/6 J wildtype mice treated with either cyclosporine A, voclosporin or solvent control. We employed endoscopy, histochemistry, immunofluorescence, bead-based multiplex immunoassays and flow cytometry to study the therapeutic effect of calcineurin inhibitors in a preventive setting. Results: Acute colitis was induced by dextran sodium sulfate characterized by weight loss, diarrhea, mucosal erosions and rectal bleeding. Both cyclosporine A and voclosporin strongly ameliorated the course of disease and reduced colitis severity in a similar manner. Conclusion: Voclosporin was identified as biologically effective in a preclinical model of colitis and may be a potential therapeutic option in treating acute severe steroid-refractory ulcerative colitis.
CRIS-Team Scopus Importer:2023-07-28
Keywords: calcineurin inhibitors; IBD; steroid refractory colitis; ulcerative colitis; voclosporin